Rancangan Materi Statistika Terintegrasi Nilai dan Budaya Keislaman: Sebuah Kerangka Konseptual - Khairiani Idris (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2021)
Abstract:Lecturers in the Islamic Universities in Indonesia have hardly found statistics textbooks that emphasize statistical literacy and use data contexts not contradict Islamic cultures. This is a research and development study aimed at developing a conceptual framework that can be referred to in designing statistics learning materials based on statistical literacy integrated with Islamic values and cultures. The phases of the study included problem analysis on statistics learning materials in Indonesia, literature reviews, developing the initial stage of a conceptual framework, validation, and revision. The result was the conceptual framework composed of five components: a) learning statistics for a virtuous character, b) learning statistics gradually and in sequences, c) learning using useful contexts, d) knowing istiqra’ in inferential statistics, and e) developing critical attitude towards quantitative information. Each component was subsequently elaborated into several points as examples in designing statistics learning materials. Abstrak:Dosen statistika di Perguruan Tinggi Keagamaan Islam di Indonesia umunya sulit menemukan buku rujukan statistika berbasis literasi statistik dan menyajikan konteks data yang tidak bertentangan dengan nilai dan budaya keislaman. Penelitian ini mencoba mengembangkan suatu kerangka konseptual yang dapat dijadikan acuan untuk mendesain materi statistika berbasis literasi statistik yang terintegrasi nilai dan budaya keislaman. Tahapan penelitian mencakup analisis permasalahan tentang materi perkuliahan statistika di Indonesia, kajian literatur, pengembangan kerangka konseptual tahap awal, validasi, dan revisi. Kerangka konseptual yang dihasilkan dari penelitian ini terdiri atas lima komponen: a) belajar statistika menuju akhlak mulia, b) belajar statistika dengan terurut dan bertahap, c) belajar dengan konteks yang bernilai manfaat, d) mengenal istiqra’ dalam statistika inferensial, dan e) membangun sikap kritis terhadap informasi kuantitatif. Setiap komponen kemudian dijabarkan dalam bentuk poin-poin yang dapat diterapkan dalam pengembangan materi statistika.